Implementasi Etika dan Bisnis Islam dalam Pemasaran Produk Skincare Bening’s Kota Sungai Penuh - Bustami Bustami (Fakultas Syariah IAIN Kerinci, 2025)
This research aims to find out how marketing strategies affect Islamic ethics and business, both directly and indirectly. This research used a qualitative approach which was collected by asking several questions directly to clear skincare consumers and the managers of clear clinics in Sungai Penuh, with a sample of 10 clear skincare users. The variables used in this research are the concept of Islamic business ethics and product marketing. The first stage is to find out what the product marketing concept is with questions regarding consumer confidence in product quality, brand image, and consumers' need for skincare. By analyzing and interviewing, we can find out how the marketing concept and influence on product use by consumers is real and based on facts. This research data was analyzed by conducting interviews by asking several questions to clear users.